INTEGRAL STUDY OF THE SILK ROADS ARE COMMERCIAL BUSINESS - Lestari, Bernadetta (Fakultas Ekonomi Universitas PGRI Adi Buana, 2010)
The Silk Roads over land, sea or the steppe, were above all a means of communication and dialogue between civilizations. The exsistence of the routes, whose origins are lost in the mists of time, but whose history can be traced back over more than 2000 years, made an inestimable contribution to the civilization of mankind. At their peak, the Silk Roads took on a significance which was both cultural and commercial. It seemed almost as if the western gate of the city of Chang